2018
DOI: 10.12659/msm.909442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resourcefulness Training on Symptoms Distress of Patients with Nasopharyngeal Carcinoma

Abstract: BackgroundSymptom distress is very common in patients with nasopharyngeal carcinoma (NPC) during radiotherapy, seriously affecting their quality of life and impeding the process of rehabilitation. Resourcefulness training can enhance the level of resourcefulness and benefit-finding, palliate symptom distress, and promote disease rehabilitation. However, the effects of resourcefulness training on local complications and benefit-finding in NPC patients during radiotherapy remains poorly understood.Material/Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In the current study, there was a positive relationship between resourcefulness and QoL, with resourcefulness being the determinant of QoL. This result is similar to studies indicating that patients with higher resourcefulness are more likely to have satisfactory QoL (Huang, Gui, et al, ; Lin et al, ). Personal resourcefulness skills indicate the ability of patients to use cognitive reconstruction, positive cognition, problem management, setting priorities and planning ahead (Zauszniewski, , ), and patients could benefit from learning such skills (Bekhet & Zauszniewski, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, there was a positive relationship between resourcefulness and QoL, with resourcefulness being the determinant of QoL. This result is similar to studies indicating that patients with higher resourcefulness are more likely to have satisfactory QoL (Huang, Gui, et al, ; Lin et al, ). Personal resourcefulness skills indicate the ability of patients to use cognitive reconstruction, positive cognition, problem management, setting priorities and planning ahead (Zauszniewski, , ), and patients could benefit from learning such skills (Bekhet & Zauszniewski, ).…”
Section: Discussionsupporting
confidence: 89%
“…Supported employment for patients who have motivation to work should be provided to advance their readiness and remove barriers. Symptom management programmes help patients acquire knowledge and skills to cope with their disease; additionally, research has indicated that teaching clients to enhance their resourcefulness skills is beneficial for their life in promoting their physical, psychological and social health (Bekhet & Zauszniewski, ; Huang, Gui, et al, ). Therefore, resourcefulness training based on Zauszniewski's resourcefulness and quality of life theory for schizophrenic patients in a systematic way is recommended, leading to patients benefiting from introduced community rehabilitation programmes to enhance their resourcefulness and QoL.…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
“…Previous studies have shown that there is a significant correlation between coping styles and resourcefulness [26,50,51]. Patients usually choose negative coping styles when their resourcefulness level is relatively low [51].…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al [50] implemented 8 weeks of resourceful training for patients with coronary heart disease in the community and found that it can reduce patients' negative coping styles and enable patients to cope with the disease using a positive attitude. Huang et al [26] improved the emotional control and coping ability of patients with nasopharyngeal carcinoma during radiotherapy through resourceful training. However, the subjects of these studies were patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation